Penetapan Kadar Flavonoid Total Buah Dengen (Dillenia serrata) Menggunakan Metode Spektrofotometri UV-Vis - ARMELIA RHAIHANA BACHTIAR (Makassar Natural Product Journal (MNPJ), 2023)
Dengen fruit juice (Dillernia serrata) is a type of medicinal plant that is used as an anti-inflammatory, antioxidant, antimicrobial, antitumor, anti-ulcer, immunoprevention, cancer chemoprevention, medicine for thrush, vomiting blood, fever, and wound medicine because it contains polyphenolic compounds, such as tannins. and flavonoids. This study aims to interpret the total flavonoid content of dengen fruit (Dillenia serrata) using the UV-VIS spectrophotometry method. This type of research is laboratory experimental using a spectrophotometer method based on the determination of extract levels and quarcetin standards. The stages of this research began with sample preparation, qualitative testing of flavonoid compounds, and ended with the determination of total flavonoid content of the sample and quarcetin standard. This study obtained the results that the positive dengen fruit extract contained flavonoids based on the results of identification using wilstater reagents, this sample also tested positive for flavonoids based on the TLC test using AlCl3 reagents and citroborate with an Rf value of 0.636, and on the quantitative test results using extract UV-VIS spectrophotometry Dengen fruit has a percentage of flavonoids of 19.355%.